Ethnopharmacological, Phytochemistry and Pharmacological Activities of Psoralea Corylifolia: A Review - Singh, Saurabh; Agrawal, Aaditi (International Research Journal of Ayurveda & Yoga, 2022)
The Indian medicinal plant Psoralea corylifolia has been used in the traditional Ayurvedic system of treatment for thousands of years. In classical Ayurvedic sources, it is referred to as ’Bakuchi’. It is also referred as Kustanaghini ,Kustanashini due to its potent effect in skin disorders. It’s an erect annual herbaceous plant of the Fabaceae family, native to China & South Africa, also it grows all across the Indian subcontinent (Maharashtra, West Bengal, Uttar Pradesh, Rajasthan, Karnataka, Bihar, and Deccan). Bakuchi root are used for dental carries; its leaves for diarrhea; and fruits for anemia, asthma, bronchitis, dysuria, improving hair and complexion, inflammation, piles, and vomiting, Its seeds are used for the treatment of scabies, ulcers, vitiligo, leukoderma, eczema, leprosy, and psoriasis. Phytochemical investigation indicates the presence of flavonoids, coumarins, quinones, phenols, benzofurans and benzopyrans, sesquiterpenoids, triterpenes, and steroids. Anti-inflammatory, hepatoprotective, hemostatic, anti-oxidant, anti-microbial, antibacterial, anti-fungal, anti-obesity, anti-viral, anti-mutagenic, anti-filarial, estrogenic, anti-cancer, anti-asthma, anti diabetic, anti-aging and immune-modulatory effects have been found for various parts of the plant. It is also effective in Alzehimer’s disease and alopecia areata. Various formulations are present in market such as babchi churna, psoralea ointment, babchi oil, bakuchi capsule, bakuchi vati, somaraji taila & avalgujadi lepa. So, an attempt has been made in this article to gathered all the possible significant information about the Bakuchi.